2022
DOI: 10.1108/ijphm-11-2020-0099
|View full text |Cite
|
Sign up to set email alerts
|

Exploring home health-care robots adoption in Malaysia: extending the UTAUT model

Abstract: Purpose This study aims to examine the possible factors affecting Malaysians’ intention to adopt new technology such as home health-care robots (HHRs) based on the extended unified theory of acceptance and use of technology (UTAUT) model. The variable price, awareness and alternative attractiveness were added since HHRs is a new technology in Malaysia. Design/methodology/approach This study collected the self-administered questionnaire from 316 respondents who are currently taking care of elderly or disabled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Performance expectations are a rich variable based on perceived usefulness, and their significant effect on user adoption has been confirmed by several studies [ 41 , 42 , 43 , 44 , 45 , 46 ]. For example, Prasetyo et al [ 41 ] confirmed that performance expectations had a positive effect on behavioral intentions to receive medical-educational e-learning and found that performance expectations had the greatest effect on behavioral intentions; Oliveira et al [ 43 ] confirmed in their empirical study that performance expectations had a positive relationship with behavioral intentions.…”
Section: Research Hypothesis and Methodologymentioning
confidence: 85%
“…Performance expectations are a rich variable based on perceived usefulness, and their significant effect on user adoption has been confirmed by several studies [ 41 , 42 , 43 , 44 , 45 , 46 ]. For example, Prasetyo et al [ 41 ] confirmed that performance expectations had a positive effect on behavioral intentions to receive medical-educational e-learning and found that performance expectations had the greatest effect on behavioral intentions; Oliveira et al [ 43 ] confirmed in their empirical study that performance expectations had a positive relationship with behavioral intentions.…”
Section: Research Hypothesis and Methodologymentioning
confidence: 85%
“…Bulamu et al (2019) further strengthen the findings that health costs borne directly by consumers will impact the probability of an endoscope screen test for dysplasia and early cancer detection. Yeoh and Chin (2022) find that price significantly influences the IJPHM 18,1 intention to adopt health-care robots in Malaysia, whereas a health-care cost study in Vietnam shows that consumers are reluctant to pay for health services above US$90 (Vuong et al, 2018). Consumer-driven health plans are said to encourage cost consciousness in customers by referencing value when making a decision.…”
Section: Empirical Review and Hypotheses Developmentmentioning
confidence: 99%
“…Remote care is defined as the use of 5G communication network technologies and software to transmit health and medical information for patients in need of urgent treatment across different locations, and to support communication and learning among medical teams from various countries globally, thereby enhancing the quality of remote medical care services and extending them to home life support [6]. Currently, Taiwan's remote care market can be categorized into three main types:…”
Section: Categories Of Remote Carementioning
confidence: 99%